The Impact of Site Elements to Micro-Climate Air Temperature - Puraprom, Wuttigarn (Journal of Architectural/Planning Research and Studies (JARS), 2016)
Global warming effect has been a serious issue for decades. The impact of site element is one of influ-ence factors in architectural design and energy conservation. This study focused on material heat capacity properties of wet grass (0.7 Btu/oF), wet-soil (0.6 Btu/oF), concrete (0.23 Btu/ oF) and dry-soil (0.19 Btu/oF) surfaces. Outdoor air temperature was influenced by those selected materials. Air temperature data were collected for 24 hours. During daytime, those surfaces received heat from solar radiation in a range of 240 to 260 Btu/ft2/h It is found that outside air temperature among wet-grass surface had raised 0.9oC similar to wet-soil as 1.8oC while concrete 2.6oC and dry-soil 2.9oC. This illustrates that high heat capacity outdoor surfaces have less effected to raise air temperature than the others. Shades can reduce air temperature cov-ered dry-soil and concrete ground by 3.7oC and 4.9oC, respectively. Therefore, it can be concluded that to reduce outdoor air temperature, those materials should have high heat capacity property and shade from vegetation can shield materials with low heat capacity. It has less effect outdoor air temperature raise which cause energy conservation in building.